Gabriela, clove and cinnamon (1988 [1962]), de Jorge Amado: tradução dos marcadores culturais para o inglês – entre a revelação e o ocultamento - Antunes, Keven de Almeida (2022)
In this dissertation we condute a lexical study of the Cultural Markers presents in the parallel corpus constituted by the novel Gabriela, cravo e canela (2006 [1958]), by Jorge Amado, with its translation into English, Gabriela, clove and cinnamon (1988 [1962]), made by James L. Taylor and William Grossman, in order to verify how the passage of culture, lexically marked, from the original to the translation occurred. For that, the cultural markers were collated with the help of the Wordsmith Tools 7.0 software, especially the Wordlist and Concord tools. The research has an interdisciplinary character and is based on the theoretical-methodological assumptions of lexicon studies with Biderman (1998), Barbosa (2001) and Oliveira and Isquerdo (2008); of Translation Modalities with Aubert (1991; 2006) and Widman and Zavaglia (2017); of Cultural Markers with Aubert (2003; 2006); Cultural Domains with Aubert (1998; 2006) and Martins and Camargo (2008); on the translation strategies of foreignization and domestication with Venuti (1992; 1995) and Berman (2007); linguistic culture with contributions from Matoré (1953), Silva (2000), Silva (2012) and Santos (2013); cultural representation by Chartier (1991), Gumbrecht (2003) and Barros (2005); Corpus Linguistics with Berber Sardinha (2000; 2004; 2009); and the Lexicographic Sheet proposed by Nascimento and Barreiros (2018). The research developed resulted in the cataloging of 104 Cultural Markers presented and classified based on the domain of culture, translation modality and domestication or foreignization strategy, organized in lexicographic sheets. The Cultural Markers presented highlighted, in the foreground, the regional linguistic characteristics presented in Jorge Amado's novel, making the author's novelistic writing a way of exposing and preserving the hybrid and mestizo culture that characterizes us as Brazilians/Baianos. In the analysis of the translation, we found that the translation modality adaptation was the most used in the novel in its English language version, especially in cultural markers that represent Afro- Brazilian culture. From this, we built a bilingual glossary that includes this Afro-descendant lexical group. This fact allows us to state that Gabriela, clove and cinnamon (1988 [1962]) is characterized as a domesticated translation, revealing that translation can also be an act of maintaining coloniality. Based on the analyzes and results obtained, we hope that this dissertation can contribute to future analysis of translations and research in the areas of lexical studies, culture and the Afro-Brazilian lexicon, to highlight the potential, whether colonizing or decolonizing, of this intercultural practice that represents the translation process.